THE RELATIONSHIP BETWEEN STUDENTS' COGNITIVE ACHIEVEMENT IN PAI SUBJECTS AND THEIR RELIGIOUS ATTITUDES AT SDN 90 CIBIRU PANYILEUKAN DISTRICT BANDUNG - Robaeah, Wilam Nafilah; Karman, Karman; Nasir, Tatang Muh; Turwanto, Teguh; Yulistiawati, Lilis (Program Studi PGMI, 2023)
It cannot be denied, someone who has high religious knowledge is directly proportional to their high religious attitude, and vice versa. That is, to what extent they can accept the at-tainment of religious knowledge that they have to apply. This study aims to: 1) determine stu-dents' cognitive achievement in PAI subject in class VI SDN 90 Cibiru; 2) knowing the reli-gious attitudes of students in PAI subjects in class VI SDN 90 Cibiru; and 3) knowing the re-lationship between students' cognitive achievement in PAI subjects and their religious atti-tudes in class VI SDN 90 Cibiru . The approach used in this study is a quantitative approach to the correlative descriptive method. Analysis of the data used through statistical calcula-tions. Data collection techniques used were questionnaires, observations, documentation studies, literature studies, and interviews. The sample used was class VI students. Where sampling was used 10% -15% of the existing population, that is, from 257 populations, 30 samples were used. The results of the study show that: 1) based on the calculation of cogni-tive achievement of students, the price (81.99) is identified in the very good category; 2) The students' religious attitudes based on calculations obtained prices (3.58) identified in the high category; and 3) the relationship between students' cognitive achievement and their religious attitude through Spearman's rank correlation test obtained the correlation value (0.188) as-sumed to be in the very low relationship category, then compared with the price of ρ table (0.306) then Ho is accepted and Ha is rejected. Then determine the price of it with a: 5%. obtained the value of t count (1.01) and t table (1.697).